Integer Programming for Solving Hospital Hypertension Patient Menu Planning - Muhammad, Nurul Ain; Muhammad, Nurul Ain (Enhanced Knowledge in Sciences and Technology, 2026)
The Delete-Reshuffle Algorithm (DRA) and an Integer Programming (IP) model are combined in this study to develop an ideal seven-day food plan for hypertension patients in Malaysian hospitals. The RNI 2017 standards' requirements for six key nutrients such as sodium, protein, potassium, vitamin B2, calcium, and vitamin C are met while minimizing expenses using a database of 426 Malaysian items in ten categories. Using MATLAB R2025b, the model produced a weekly plan that cost RM 151.20 (RM 21.60 per day) and included 126 different meals spread over six different occasions each day, ensuring full dietary diversity. All nutrients met RNI standards, and daily salt intake was kept considerably below the 2000 mg limit, ranging from 556 to 1717 mg. While preserving cost-effectiveness and nutritional compliance, the DRA effectively removed meal repetitions. With the help of this framework, hospital meal plans that are clinically acceptable, economical, and culturally relevant can be created through mathematical optimization.